Konsep Kafalah dalam Fiqh Klasik dan Aplikasinya pada Sistem Jaminan Syariah Kontemporer - Ummi Sa’adah; Muhamad Zen (Universitas 45 Surabaya, 2025)
Kafalah is an important instrument of Islamic jurisprudence (fiqh) in Islamic economic law, particularly in Islamic banking, Islamic insurance (takaful), and Islamic fintech as a sharia-compliant guarantee mechanism. This article aims to examine the application of kafalah in the economic sector and its implementation in contemporary Islamic guarantee systems. The methods used are literature studies and the review of several case studies and scientific articles. This article finds that in its implementation, modern kafalah is still in line with the classical principle of amanah (trustworthiness) because both are rooted in the values ​​of trust, responsibility, and mutual support, even though modern kafalah is commercial in nature. Several contemporary scholars, including the DSN-MUI fatwa No. 11/DSN-MUI/IV/2000, permit the imposition of administrative fees as long as they are not profit-oriented but only cover real costs. The application of modern kafalah remains in accordance with classical fiqh principles as long as they maintain the principles of amanah (trustworthiness), transparency, and do not contain riba (usury) or gharar (gharar). Therefore, it is important to harmonize national regulations to ensure that kafalah practices continue to run in accordance with the maqasid of sharia and support the development of Islamic financial progress while still being able to maintain public trust in the Islamic financial system.